Pemetaan persebaran perkebunan kelapa Berbasis sistem informasi Geografis: Pemetaan persebaran perkebunan kelapa berbasis sistem informasi geografis - Merentek, Stevenly; Tooy, Dedie; Pakasi, Sandra (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aims to map coconut plantations in Tondei Village using onscreen visual interpretation, determine the area of coconut plantations in Tondei Village and determine the land cover of coconut plantations. The method used is on-screen visual classification by utilizing SAS Planet image data, Google Earth imagery, RBI Maps, and digitized with a geographic information system using ArGis 10.8 software. The results of the on-screen image visual interpretation analysis show a map of the distribution of coconut plantations spread across Tondei Village. The results of spatial mapping are generated based on several elements of visual interpretation such as patterns, shapes, location textures and associations. The results of the visual image interpretation analysis on the screen show that the spatial mapping of coconut plantation land in Tondei Village has an area of 210.88 Ha, mixed plantation land area of 148.54 Ha, shrub land area of 78.93 Ha, and open land area of 92.36 Ha.